PERLINDUNGAN KERJA BAGI PEKERJA PEREMPUAN DALAM SUATU PERUSAHAAN DITINJAU DARI PASAL 81 s/d PASAL 83 UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Pramita Dewi, Ni Luh; Markeling, I Ketut; Dharmakusuma, A.A.GA (Kertha Wicara : Journal Ilmu Hukum, 2013)
The implementation of articles 81 to 83 of The Act number 13 Year 2003to female workers at a company have been performed quite properly. It is muchhoped by the government, in particular by the entrepreneurs as well as theworkers. The regulations for protecting female workers require single policy fromthe entrepreneurs and they also have to build good relations to the governments,the Manpower Department because all policies issued by the entrepreneurscannot be separated from the government's controls to prevent illegal actionsdone by the entrepreneurs.Problems and barriers found by a company in performing the Articles 81to 83 of the Act number 13 Year 2003 are realized in a form providing leafconsidering that women have natures weaker than men and they experience theirnatural habits, such as menstruation, pregnant, and giving birth. In overcomingthe problems and the barriers, companies have tried hard in realizing the essenceof the Articles 81 to 83 of the Indonesian Constitutions Number 13 Year 2003 inthe forms providing leaves of menstruations, pregnancies, and giving births whichare performed after a discussion with the representative of the female workers.
Keywords: Job protection, Women Worker.